Pengaruh Disiplin dan Keselamatan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan Pada PT Cici Farma Unit Produksi Farmasi Bekasi - Yusrizal; Eliza (Jurnal Pajak dan Bisnis, 2020)
This study aims to determine and analyze the effect of discipline and Occupational Health and Safety (K3) partially and simultaneously on employee performance at PT.Cici Farma Pharmaceutical Production Unit Bekasi. The approach used in this research is quantitative research and the strategy used in this research is the associative strategy. The research method that will be used is descriptive analysis method using regression analysis, namely to determine how much the contribution / influence of discipline and occupational health and safety (K3) to the performance of employees at PT.Cici Farma Pharmaceutical Production Unit Bekasi. In this study, data processing was carried out using SPSS ver. 24.00. The population in this study were all employees of PT.Cici Farma Bekasi Pharmacy Production Unit, amounting to 52 people. The sample used is based on sensory techniques as many as 52 employees at PT.Cici Farma Pharmaceutical Production Unit Bekasi. Based on the analysis and discussion, it shows that discipline has a significant positive effect on employee performance at PT.Cici Farma Pharmaceutical Production Unit Bekasi, it can be seen that a significant value of 0.000 <0.05, the first hypothesis (H1) is accepted; Occupational Health Safety (K3) has a significant positive effect on employee performance at PT.Cici Farma Bekasi Pharmacy Production Unit, it can be seen that a significant value of 0.044 <0.05, the second hypothesis (H2) is accepted and simultaneously discipline and Occupational Health Safety (K3) have a significant positive effect on employee performance at PT.Cici Farma Bekasi Pharmacy Production Unit with a significant value of 0.000 <0.05, the third hypothesis (H3) is accepted.